2007
DOI: 10.1111/j.1365-3083.2007.01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Tumour‐associated Dendritic Cells into Endothelial‐like Cells: An Alternative Pathway of Tumour Angiogenesis

Abstract: Until recently, the only accepted mechanism of tumour vascularization was the sprouting of endothelial cells (EC) from pre-existing vessels, while recent studies suggest the contribution of stem cell-derived endothelial progenitors as well as cells from the myeloid lineage. Here, we show a new way of endothelial differentiation that involves the specific modulation of monocytes by the tumour environment. The tumour milieu is characterized by the presence of cytokines and lactate which induce the differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…Tumor-associated DCs (TADCs) incubated additionally with VEGF and oncostatin M could trans-differentiate into endothelial-like cells (ELCs), which might be an alternative pathway of tumor angiogenesis (6). These reports show that DC progenitor or DCs can trans-differentiate into ELCs, possibly contributing to vasculogenesis in the adult.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Tumor-associated DCs (TADCs) incubated additionally with VEGF and oncostatin M could trans-differentiate into endothelial-like cells (ELCs), which might be an alternative pathway of tumor angiogenesis (6). These reports show that DC progenitor or DCs can trans-differentiate into ELCs, possibly contributing to vasculogenesis in the adult.…”
Section: Introductionmentioning
confidence: 91%
“…Addition of conditioned medium of murine Lewis lung carcinoma cells was used to investigate the CD34 + cells' differentiation (5). It has been shown that the tumor microenvironment characterized by the presence of cytokines and lactate can induce monocytes to transdifferentiate into ELCs in the presence of pro-angiogenic mediators (6,9). These methods can simulate the tumor microenvironment to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DCs are cells specialized in triggering immune responses, they have been shown to participate in pathological conditions such as cancer and atherosclerosis 4,15,16 . They have been also claimed to participate in angiogenic process 17,18 , even suggested as structurally participating in the developing of new vessels 19,20 . Thus, methods that allow for DC tracking in vivo, and determining their geographical localization in different tissues 4,21,22 are very valuable.…”
Section: Discussionmentioning
confidence: 99%